Title Observational constraints on the kinetics of the ClO-BrO and ClO-ClO ozone loss cycles in the Arctic winter stratosphere - Butz, A.; Bosch, H.; Camy-Peyret, C.; Dorf, M.; Engel, A.; Payen, Sébastien; Pfeilsticker, K. (Geophysical Research Letters, 2007)
International audience